74.4k views
2 votes
PLEASE HELP ASAP 25 PTS ):

PLEASE HELP ASAP 25 PTS ):-example-1
User Rexroxm
by
5.7k points

1 Answer

4 votes

Answer:

- 59

Explanation:

note that (f ○ g)(x) = f(g(x))

To find f(g(x)) substitute x = g(x) into f(x)

f(- 4x + 6)

= - 2(- 4x + 6) - 7

= 8x - 12 - 7 = 8x - 19

to evaluate f(g)(- 5) substitute x = - 5

= (8 × - 5) - 19 = - 40 - 19 = - 59


User Kingsley Mitchell
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.